Tau and Membranes: Interactions That Promote Folding and Condensation - Sallaberry, Chad A.; Voss, Barbie J.; Majewski, Jaroslaw; Biernat, Jacek; Mandelkow, Eckhard; Chi, Eva Y.; Vander Zanden, Crystal M. (Frontiers in Cell and Developmental Biology, 2021)
Tau misfolding and assembly is linked to a number of neurodegenerative diseases collectively described as tauopathies, including Alzheimer’s disease and Parkinson’s disease. Anionic cellular membranes, such as the cytosolic leaflet of the plasma membrane, are sites that concentrate and neutralize tau, primarily due to electrostatic interactions with tau’s microtubule binding repeat domain. In addition to electrostatic interactions with lipids, tau also has interactions with membrane proteins, which are important for tau’s cellular functions. Tau also interacts with lipid tails to facilitate direct translocation across the membrane and can form stable protein-lipid complexes involved in cell-to-cell transport. Concentrated tau monomers at the membrane surface can form reversible condensates, change secondary structures, and induce oligomers, which may eventually undergo irreversible crosslinking and fibril formation. These β-sheet rich tau structures are capable of disrupting membrane organization and are toxic in cell-based assays. Given the evidence for relevant membrane-based tau assembly, we review the emerging hypothesis that polyanionic membranes may serve as a site for phase-separated tau condensation. Membrane-mediated phase separation may have important implications for regulating tau folding/misfolding, and may be a powerful mechanism to spatially direct tau for native membrane-mediated functions.